2015
DOI: 10.1089/cap.2014.0073
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Presentation of Pediatric Autoimmune Neuropsychiatric Disorders Associated with Streptococcal infections in Research and Community Settings

Abstract: Background: The first cases of pediatric autoimmune neuropsychiatric disorders associated with streptococcal infections (PANDAS) were described > 15 years ago. Since that time, the literature has been divided between studies that successfully demonstrate an etiologic relationship between Group A streptococcal (GAS) infections and childhood-onset obsessivecompulsive disorder (OCD), and those that fail to find an association. One possible explanation for the conflicting reports is that the diagnostic criteria pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
79
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(82 citation statements)
references
References 23 publications
1
79
0
2
Order By: Relevance
“…All subjects had received therapeutic doses of antibiotics without relief of symptoms, but all were maintained on antibiotic prophylaxis throughout the treatment period. Ten of the 35 patients (29%) described here are also included in a report of clinical characteristics of a larger sample (n = 40) of children and adolescents with PANDAS (Swedo et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…All subjects had received therapeutic doses of antibiotics without relief of symptoms, but all were maintained on antibiotic prophylaxis throughout the treatment period. Ten of the 35 patients (29%) described here are also included in a report of clinical characteristics of a larger sample (n = 40) of children and adolescents with PANDAS (Swedo et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…The diagnostic criteria are as follows: (1) presence of obsessive-compulsive disorder and/or a tic disorder, (2) pediatric onset of symptoms (age 3 years to puberty), (3) episodic course of symptom severity, (4) association with group A beta-hemolytic streptococcal infection (a positive throat culture for strep or history of scarlet fever), and (5) association with neurological abnormalities (motoric hyperactivity or adventitious movements, such as choreiform movements) [44]. In addition, children may also have the following associated symptoms: (1) Attention deficit hyperactivity disorder (ADHD) symptoms (hyperactivity, inattention, fidgety), (2) separation anxiety (child is Bclingy^and has difficulty separating from his/her caregivers; for example, the child may not want to be in a different room in the house from his/her parents), (3) mood changes (irritability, sadness, emotional lability), (4) sleep disturbance, (5) nighttime bed wetting and/or daytime urinary frequency, (6) fine/gross motor changes (e.g., changes in handwriting), and (7) joint pains [44]. MRI volumetric analysis of patients fulfilling PANDAS diagnostic criteria includes an 8 % increase in caudate volume, 7 % increase in pallidal volume, and 5 % increase in putaminal volume [45].…”
Section: Pediatric Autoimmune Neuropsychiatric Disorders Associated Wmentioning
confidence: 99%
“…5 Five clinical criteria were established: presence of obsessive compulsive disorder (OCD) or tic disorder; pre-pubertal onset; acute symptom onset and episodic (relapsing-remitting) course; presence of associated neurological abnormalities (particularly choreiform movements), and temporal association with group A streptococcal (GAS) infection. 5,6 The diagnosis of PANDAS has been a cause for debate with some evidence supporting it [5][6][7] while others question it. 8,9 Here, we present the case of our patient who initially presented to services when he was 11 years old and document and discuss his presentation and treatment over the following seven years.…”
mentioning
confidence: 99%
“…14,15 Both these studies have shown little support for the PANDAS hypothesis. 6 There have been several case reports linking PANDAS and other infectious illness with certain eating disorders. 10,17,18 Our case adds to these as well as to the idea that there may be other manifestations of PANDAS as well as OCD symptoms, although our patient had a longer period of illness overall than other reported cases.…”
mentioning
confidence: 99%